Модификация фенилаланил-тРНК-синтетазы из E. coli с помощью 1,N6-этеноаденозин-5'-трифосфата - Подуст, В.И.; Невинский, Г.А.; Лаврик, О.И. (Биополимеры и клетка, 1985)
Данные о фотохимических превращениях флюоресцирующего аналога АТР—1, N⁶-этеноаденозин-5'-трифосфата — отсутствуют в литературе. В данной работе впервые показаны инактивация фермента и ковалентное присоединение к нему ΣАТР на примере фенилаланил-тРНК-синтетазы из Е. coli при облучении монохроматическим светом азотного лазера с длиной волны 337 нм. Дані щодо фотохімічних перетворень флуоресціюючогого аналога АТР ? 1, N⁶-етеноаденозин-5'-трифосфату – відсутні в літературі. У представленій роботі вперше показано інактивацію ферменту і ковалентне приєднання до нього ΣАТР на прикладі фенілаланіл-тРНК-синтетази з Е. coli за опромінення монохроматичним світлом азотного лазера з довжиною хвилі 337 нм. The irradiation of phenylalanyl-tRNA synthetase by nitrogen laser light (X337 nm) in the presence of e ATP results in enzyme inactivation and covalent attachement of nucleotide to the protein. Dependence of the enzyme photoinactivation rate on the eATP concentration is of saturated character. ATP partially protects the enzyme against covalent attachement of eATP. However none of the specific ligands (ATP, Phe, phenylalanyladenylate) prevents the enzyme inactivation.